Portraits of medieval Europe, 800-1400
1 online resource
Keywords: "This volume provides a collection of 'imagined lives'-individuals who, no matter their position on the social hierarchy, were crucial to the development of medieval Europe and the modern period that followed. Based on primary source materials and the latest historical research, these literary accounts of otherwise unsourced or under-sourced individuals are written by leading scholars in the field. The book's approach transcends the limitations of both historical narrative and literary fiction, offering a research-informed presentation of real people that is enriched by informed speculation and creative storytelling. This enriched presentation of the lives of these individuals offers the quickest route to understanding medieval culture, society, and intellectual thought. Crucially, the book treats the whole of Europe, broadly defined: both conventional areas of study such as England and France, and also lesser studied but no less important areas such as eastern Europe, Iberia, and the Balkans. The reader of Portraits of Medieval Europe encounters the diversity present in the European past: the resulting portraits-unique, personal, and engaging-offer not only a wide geographical scope, but also perspective on the formation of European society in its fullest form. This book is an accessible and engaging for students new to medieval history as well as those wishing to expand their knowledge of medieval society"--